P–495 Telemedicine in ART during SARS-CoV–2 pandemic : far and yet close. (6th August 2021) - Stigliani, S; Massarotti, C; Maccarini, E; Sozzi, F; Scaruffi, P; Anserini, P
Abstract: Study question: Could telemedicine help in the management of the infertile couple's path at a fertility center? Summary answer: The introduction of telemedicine increased the number of cycles within 6 months from the first consultation and reduced the drop-out rate. What is known already: In Italy during the complete lockdown due to the first pandemic wave of SARS-CoV–2 the activity of fertility centers were stopped, with the exception of fertility preservation procedures for oncological patients. We therefore proposed a service of telemedicine to our patients, that we called SmartPMA. Study design, size, duration: A longitudinal study performed at a public infertility center. The SmartPMA service was offered to 93 couples referred to our center from March 9th to May 31st, 2020. Initially 72 couples was interested in SmartPMA. Our center gradually re-opened and the first oocytes retrieval was performed on June 9th . Participants/materials, setting, methods: Sixty-one out of 72 couples (85%) performed the SmartPMA from April 7th to June 16th, 2020. After acquiring informed consent and sending two anamnestic questionnaires, we booked a video-consultation with a gynecologist and a biologist. Afterwards, we sent medical prescriptions for appropriate clinical tests. At the re-opening, we offered the chance to start the ART cycle. Time to the first treatment and drop-out rates were compared to historical controls (2017–2019) using chi-square test. Main results and the role of chance: Eleven couples declined the SmartPMA and booked an appointment at the reopening. Only 2 of these couples (18%) actually performed an IVF treatment within six months. Three out the 61 couples that accepted the SmartPMA did not perform IVF treatments because the age of women exceeded the legal limit to access to a public ART center. Twelve out of 58 couples (21%) did not performed any IVF treatment for the following reasons: 4 women spontaneously got pregnant, 1 couple gave up for medical reasons, 3 were referred to ovodonation, and 4 were lost to follow-up. Thirty-eight out of 58 couples (66%) (median age of woman: 36 + 4 years, range 27–43) performed at least one ART treatment (14 IUI, 12 ICSI cycle, 12 FIVET cycle). Eight out of 58 couples (14%) needed further clinical tests and their treatments are ongoing. The mean time to first treatment in the SmartPMA couples was 4 + 1 months (range 1–6). After SmartPMA, 66% of the couples performed the first cycle within 6 months, compared to 37% of controls (333/898 couples at their first access to our center from 2017 to 2019), p < 0.00001. The drop-out was reduced from 39% to 20%, p = 0 .0038. Limitations, reasons for caution: We cannot exclude that the couples that joined the SmartPMA service during the pandemic period were particularly motivated to perform IVF treatments. We are aware of the small sample size and that this is a monocentric study. Wider implications of the findings: Even after the pandemic, telemedicine can be an useful tool for fertility centers to reduce the discomfort of several visits in hospital, without losing patients but rather ultimately reducing the time to treatments and drop-out. Trial registration number: Not applicable